Africans' response to the January 2023 Omicron variant wave in China: the impact of COVID-19 vaccination status - Erick Thokerunga; Peter Kisembo; Manzama-Esso Abi; Fangnon Firmin Fangninou; Juval Avala Ntsigouaye; Janet Oluwasola Bolorunduro; Chinaza Valerie Olovo; Marvellous Okeke; Samuel Emeka Peter; Innocent Okohi Agida; Moses Kumi; Emmanuel Kwateng Drokow; et al. (SpringerOpen, 2024)
Abstract Introduction The January 2023 COVID-19 omicron wave in China garnered wide publicity partly because it evaded most vaccines at that time and resulted in "breakthrough infections" in previously vaccinated individuals. This study focused on the COVID-19 vaccination status and the response of foreigners of African descent who were in China during the January 2023 Omicron-driven COVID-19 wave. Materials and methods A cross-sectional online survey of Africans in China was conducted in January 2023. Self-report electronic questionnaires were sent to eligible participants across the country, with no restriction on age, gender, or country of origin. Two hundred sixty-six participants were eventually enrolled. Collected data was cleaned and analyzed using SPSS. Descriptive analysis was used to summarize the data in terms of numbers and percentages, while the Chi-square test was used to determine relationships among variables. Results A total of 266 participants were enrolled, 68.8% males and 31.2% females. The majority (97%) were 45 years and below and mostly students (75.2%). 87.2% were vaccinated, with 53.1% having taken at least 2 shots. Sinovac (53.9%) was the most used vaccine brand. 21.4% reported infection with COVID-19 during the January 2023 omicron wave, with 14.0% reporting "breakthrough" infections. No significant difference was seen in the risk of getting infected with COVID-19 between unvaccinated and vaccinated participants; OR 1.2 (95% CI 0.396-3.634, p = 0.747). 35.1% reported mild asymptomatic infections, while 64.9% reported symptoms. The majority of the cases (89.5%) were managed from home. Conclusion In summary, most Africans in China were vaccinated during the January 2023 COVID-19 omicron wave, although "breakthrough" infections were reported. The infection rate among Africans in China was relatively higher than for African Americans and those living in Africa, but the majority were managed from home. Future studies are needed to capture vital COVID-19 information on Africans in China for more trailered responses to future outbreaks.